2006
DOI: 10.1007/s10740-006-0001-7
|View full text |Cite
|
Sign up to set email alerts
|

Transverse electric discharges in supersonic air flows: simulation of gasdynamic effects in the discharge channel

Abstract: A model of heat source is validated for the description of the gasdynamic aspects of interaction between a discharge channel and supersonic flow, which are defined by the heating of gas. The model is based on the characteristic features of a discharge in supersonic flow, which are observed in the case of nonequilibrium plasma whose conductivity is defined by the degree of ionization, namely, rapid heating of air in the electrode regions and relatively low values of reduced electric field in extended discharge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…The obtained results demonstrated that the apparently natural model of extended cylindrical source, as well as the frequently employed model of spherical source, is hardly suitable for describing the interaction between the discharge channel and flow. From the gasdynamic standpoint, the discharge "shines but not warms": the extended parts of discharge spend electric energy but do not contribute to the heating of gas [8]. Agreement with experiment in the distribution of gas temperature and flow velocity is reached for sources whose extent is several times longer than their diameter.…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…The obtained results demonstrated that the apparently natural model of extended cylindrical source, as well as the frequently employed model of spherical source, is hardly suitable for describing the interaction between the discharge channel and flow. From the gasdynamic standpoint, the discharge "shines but not warms": the extended parts of discharge spend electric energy but do not contribute to the heating of gas [8]. Agreement with experiment in the distribution of gas temperature and flow velocity is reached for sources whose extent is several times longer than their diameter.…”
Section: Introductionmentioning
confidence: 76%
“…It is associated with the mechanism of "rapid heating of gas", i.e., the heating during periods of time much shorter than the time of vibrational relaxation [6,7]. This mechanism was used in [8] to construct a simple model which treats the discharge as the zone of energy release and enables one to describe gasdynamic effects due to the heating of gas in a supersonic flow. In so doing, primary attention was given to analysis of distribution of energy input along the flow.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations